Analysis of the vibration of the vehicle body with the elimination of the influence of tires - Łukasz KONIECZNY (Scientific Journal of Silesian University of Technology. Series Transport)
The article presented the results of vibration measurements of selected elements of the vehicle during the test vibration carried out on a bench with a harmonic kinematic extortion. The results of research carried out for the car when replacing tire and wheels steel tripod eliminating the influence of elasticity and damping tires. The tests were performed at various values of the shock absorber fluid filling (from 100% to 50% of the shock absorber fluid). For registered vibration acceleration STFT analysis was performed.